Comparison of Partial- and Full-Mouth Examination in Periodontal Assessment Among Untreated Patients - R. ShariatmadarAhmadi; MJ.Kharazi Fard; V. Mousavi (Tehran University of Medical Sciences, 2009)
Objective: Whole-mouth examination is generally considered as a gold standard for exact periodontal disease assessment. Partial mouth examination also has sometimes been used for this purpose, but its efficacy has been questioned. With regard to symmetric destruction hypothesis of periodontal disease, the present study investigated the efficacy of partial- mouth examination as an alternative for whole-mouth examination. Materials and Methods: Eighty subjects aged between 20 to 61 years old (mean 41 years old, 47 males & 33 females) with periodontal disease at different stages of severity and extent (Mild, Moderate, Severe) were examined. Plaque index (PI), gingival index (GI), and papillary bleeding index (PBI) were assessed in whole-mouth except third molars, and were compared with four defined partial-mouth examinations on teeth in Upper Right/Lower Left, Upper Right/Lower Right, and Upper Left/Lower Left quadrants, as well as on Ramfjord teeth. T-test and intraclass correlation coefficients (ICC) served for statistical analysis. Results: Differences between mean PI, GI, PBI in partial and whole-mouth examination were not statistically significant (P>0.05) and agreement between partial- and wholemouth assessment was generally greater than 0.9 (ICC>0.9). However, upper right and lower left quadrants examinations showed the most consistency and conformity with whole-mouth examination. Conclusion: partial-mouth examination procedure especially in upper right and lower left quadrants might be considered as an acceptable alternative to whole mouth assessment. Partial-mouth examination procedure conserves time, limit cost and reduce the patient and examiner's fatigue while providing maximum clinical information.